The Use of Wizer.Me Learning Media to Improve Students' Mufradat Memorization at MTs Negeri 6 Boyolali - Muslihudin Muslihudin; Abid Nurhuda; Sofiah Iskanatin Janah; Farichatul Ula Safarina Farda; Dewi Sinta (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2023)
In the world of education, various kinds of technology are starting to emerge to facilitate and expedite the learning process, especially learning Arabic which is often considered difficult by most students. One of these technologies is Wizer. me, which in its journey has become a learning medium for students, but some teachers still don't know how to use it, so the purpose of this study is to describe the use of Wizer. me Learning Media in Improving Students' Mufradat Memorization at MTs Negeri 6 Boyolali (Competency Training for Arabic Language Teachers). The method used is field qualitative and uses observation techniques, interviews, and documentation when collecting data. Then analyzed the data and concluded. The results showed that the training activities included identifying problems where teachers were not optimal in using media, then planning by compiling activities to conduct wizer. me training for Arabic teachers, followed by an implementation which consisted of (Field survey, Coordination, Outreach, Tutorial Workshop, and Provision of case examples) and the last is evaluation and reflection by providing an understanding that the training should be carried out continuously so that teachers are accustomed to and can maximize learning using existing media.